Diálogo inter-religioso cristão a partir da centralidade de Jesus: impasses e perspectivas. - Siqueira, Valderêdo Clemente de (2017)
This master‟s dissertation aims to present some aspects of the itinerary followed by Christian theology in its effort to understand the relationship between Christianity and other religions, as well as to maintain an openness to dialogue with other religious traditions. The reflection takes into account the opening promoted after Vatican II, which dealt with the salvation of non-Christians and members of other religious traditions, emphasizing that this perspective does not negate or reduce the value of religious identities, especially in the case of the Christian faith, the relevance of Christ, but leads them to a deepening and maturing, motivated by dialogue and a lovely and co-responsible encounter. In the particular case of the Christian faith, as an example, it would be reinterpreted from the dialogical encounter with the other faiths. In the particular case of the Christian faith, as an example, be reinterpreted from the dialogical encounter with the other faiths. The same should occur with any religious tradition. It is considered that such a vision, in a certain sense, supplants other models such as exclusivism, which considers Jesus Christ and a Church as the exclusive way of salvation; Inclusivism, which considers Jesus Christ as the way of salvation for all, albeit implicitly; and Pluralism, which is a relativistic perspective in which Jesus is the way of salvation for christians, for others, the way is a tradition, with no greater efforts of self-criticism, revision, and mutual interpellation. In other words, all religions participate of the salvation of God, each one by himself and in his own way. The approach and the dialogue between the various religious traditions helps them to build and rebuild their founding identities and principles.